Reliability and construct validity of newly modified knowledge, attitude and practice of medical doctors on smoking cessation guidelines scales - Shalihin, Mohd Shaiful Ehsan; Nik Mohamed, Mohamad Haniki; Md Aris, Mohd Aznan (Malaysian Medical Association, 2019)
INTRODUCTION: Number of active smokers in Malaysia is increasing despite availability of stop smoking clinics and smoking cessation medications. Thus, the practice of the healthcare professionals involved in providing smoking cessation intervention using evidence based guidelines needs to be assessed using validated assessment tool. Newly invented reliable and valid questionnaire is needed to be develop locally. This study aimed to develop and validate a newly modified questionnaire to assess the knowledge, attitude and practice of medical doctors based on national smoking cessation guidelines and factors contributing to the score. METHODS: The 22 items consist of mixture of true/false choice questions and Likert scaling response based on domain of 5A’s (ask, assess, advice, assist, arrange) and 5R’s (relevant, risks, rewards, roadblocks, repetitions) of the national stop-smoking guideline. The questionnaires were distributed to 131 primary care doctors. Reliability was determined using Cronbach’s alpha for internal consistency while construct validity was assessed using factor analysis. RESULTS: A high degree of internal consistency was observed for these 22-items (Cronbach’s alpha = 0.87), with good knowledge subscale (0.72), attitude subscale (0.58) and practice subscale (0.92). Factor analysis showed five meaningful components which represent the smoking cessation framework. DISCUSSION: This study indicates that this questionnaire is most reliable and valid tool to assess the knowledge, attitude and practice on stop smoking guidelines compared to previously available questionnaire.